First you take a piss.
Once you flush, you can say your ABCs. When you get to J, the toilet should be empty. J=8.
So factoring in that 8 for 'x' = you light the BBQ grill. Since a guy cannot BBQ without a beer - open a beer. Beers have 12 oz. of liquid in them.
So the answer is 12.
2007-02-14 16:37:04
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
http://www.algebrahelp.com
Simplifying
(x + -1)(x2 + 5x + 6) = 0
Reorder the terms:
(-1 + x)(x2 + 5x + 6) = 0
Reorder the terms:
(-1 + x)(6 + 5x + x2) = 0
Multiply (-1 + x) * (6 + 5x + x2)
(-1(6 + 5x + x2) + x(6 + 5x + x2)) = 0
((6 * -1 + 5x * -1 + x2 * -1) + x(6 + 5x + x2)) = 0
((-6 + -5x + -1x2) + x(6 + 5x + x2)) = 0
(-6 + -5x + -1x2 + (6 * x + 5x * x + x2 * x)) = 0
(-6 + -5x + -1x2 + (6x + 5x2 + x3)) = 0
Reorder the terms:
(-6 + -5x + 6x + -1x2 + 5x2 + x3) = 0
Combine like terms: -5x + 6x = 1x
(-6 + 1x + -1x2 + 5x2 + x3) = 0
Combine like terms: -1x2 + 5x2 = 4x2
(-6 + 1x + 4x2 + x3) = 0
Solving
-6 + 1x + 4x2 + x3 = 0
Solving for variable 'x'.
The solution to this equation could not be determined.
2007-02-15 00:47:15
·
answer #2
·
answered by Joe 3
·
0⤊
1⤋
factor out the second part
(x-1)(x+3)(x+2)=0
x-1=0; x=-1
x+3=0; x=-3
x+2=0; x=-2
answers:
x=1, x=-3, x=-2
2007-02-15 00:39:09
·
answer #3
·
answered by Bill F 6
·
0⤊
1⤋
(x-1)(x^2+5x+6)
=(x-1)(x^2+3x+2x+6)
=(x-1) { x(x+3)+2(x+3) }
=(x-1)(x+3)(x+2)=0
x=1, x= -3, x= -2
2007-02-15 01:27:31
·
answer #4
·
answered by nazia f 4
·
0⤊
0⤋
when a*b=0
that means
a=0 or b=0 or both
then x-1=0
->x=1
or
(x^2+5x+6)=0
x1=-2;x2=-3
or both
2007-02-15 00:38:56
·
answer #5
·
answered by Suiram 2
·
0⤊
1⤋
obviously one of the solutions is x=1. to solve the quadratic, you can either plot that on a graphing calculator or use the QUADRATIC FORMULA. i don't want to sound rude, but seriously have you not learned that in math class?? use it!
2007-02-15 00:36:35
·
answer #6
·
answered by stitchfan85 6
·
0⤊
1⤋
12.1X2.5X2.5
2014-01-05 13:11:26
·
answer #7
·
answered by Trena 1
·
0⤊
0⤋